Eighteen-sector switching strategy for torque ripple reduction of direct torque controlled induction motor drive. (1st January 2011) - Gupta, R.A.; Kumar, Rajesh; Bhangale, S.V.
Direct torque control (DTC) is an emerging technique for controlling the PWM inverter-fed induction motor drives (IMDs). The low number of voltage vectors, which can be applied to the machine using the basic DTC scheme, may cause undesired torque and current ripple. This paper proposes DTC 18-sector switching strategy, where the d-q flux locus plane is divided into 18 equal sectors, which lead to an increase in the number of voltage vector. Here a modified switching table has been derived on the basis of the optimised state selection of voltage vector. The proposed scheme is simple as it does not increase the complexity in the vector selection process and is less parameters sensitive. The performance of the proposed and conventional DTC schemes has been checked at low speed in order to demonstrate the torque ripple reduction. To verify the feasibility of the proposed scheme, computer simulations and an experimental test has been carried out to validate the results of the proposed method.